The Prophetic Education Paradigm as the Scientific Integration of UIN Saifuddin Zuhri in Merdeka Belajar Policy - Moh. Roqib; Agus Husein As Sabiq (AT-TA'LIM, 2022)
This study aims to determine the prophetic education paradigm as an approach of scientific integration in the State Islamic University of Prof. KH. Saifuddin Zuhri Purwokerto (UIN Saizu) in the "Merdeka Belajar â€“ Kampus Merdeka" policy. This study employed a qualitative approach which emphasized a library research method. Data sources gathered from libraries or documents in the form of books, journal articles, translated publications, and the internet by investigating data sources concerned with the topics of scientific integration, prophetic education, and "Merdeka Belajar â€“ Kampus Merdeka" policy. The data were analyzed using descriptive and analytical investigation to describe, report, and evaluate the present situation The results of the study revealed that prophetic education is based on the idea of encouraging people to be decent (righteous), achieving the rank of perfect human being (insÄn kÄmil) and making an improvement (muslih) into an ideal environment or society (khaira ummah). Professional education is continuing to develop a new system for bringing people closer to God (transcendence) through digitally expanding human ideals (humanization) and avoiding harmful things (liberation). However, the trend of the "Merdeka Belajar" policy was capable of accommodating material data (cognitive, affective and psychomotor) but lack of spirituality. Therefore, prophetic education will be able to bridge competence and spirituality in an independent learning policy. The initiative on scientific integration must continue as a manifestation of the scientific and integrated nature of Islam through the spirit of prophetic education.